2023
DOI: 10.1097/tp.0000000000004726
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Chest CT Findings at BOS Diagnosis in Lung Transplant Recipients

Abstract: Background. Bronchiolitis obliterans syndrome (BOS) after lung transplantation is characterized by fibrotic small airway remodeling, recognizable on high-resolution computed tomography (HRCT). We studied the prognostic value of key HRCT features at BOS diagnosis after lung transplantation. Methods. The presence and severity of bronchiectasis, mucous plugging, peribronchial thickening, parenchymal anomalies, and air trapping, summarized in a total severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…CT screening of the donor organ and identifying pulmonary abnormalities in the graft even before the lung transplant was performed, resulted in identifying patterns via machine learning that were indicative of a 19 times increased risk of CLAD development [10]. Van Herck et al [11] demonstrated that the presence and severity of bronchiectasis, and high subscores for mucous plugging, peribronchial thickening or parenchymal involvement are related to worse graft survival. A high score was also associated with a shorter time to BOS onset, lower FEV 1 , forced vital capacity, more preceding airway infections, specifically with Pseudomonas aeruginosa, and increased airway inflammation [11].…”
Section: Diagnosis Of Chronic Lung Allograft Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT screening of the donor organ and identifying pulmonary abnormalities in the graft even before the lung transplant was performed, resulted in identifying patterns via machine learning that were indicative of a 19 times increased risk of CLAD development [10]. Van Herck et al [11] demonstrated that the presence and severity of bronchiectasis, and high subscores for mucous plugging, peribronchial thickening or parenchymal involvement are related to worse graft survival. A high score was also associated with a shorter time to BOS onset, lower FEV 1 , forced vital capacity, more preceding airway infections, specifically with Pseudomonas aeruginosa, and increased airway inflammation [11].…”
Section: Diagnosis Of Chronic Lung Allograft Dysfunctionmentioning
confidence: 99%
“…Van Herck et al [11] demonstrated that the presence and severity of bronchiectasis, and high subscores for mucous plugging, peribronchial thickening or parenchymal involvement are related to worse graft survival. A high score was also associated with a shorter time to BOS onset, lower FEV 1 , forced vital capacity, more preceding airway infections, specifically with Pseudomonas aeruginosa, and increased airway inflammation [11]. In another study, a machine learning tool was used to quantify ground-glass opacity, reticulation, hyperlucent lung and pulmonary vessel volume (PVV) at CLAD diagnosis for phenotyping and prognostication compared with formal radiologist scoring.…”
Section: Diagnosis Of Chronic Lung Allograft Dysfunctionmentioning
confidence: 99%
“…5,6 In this issue of Transplantation, Van Herck and colleagues offer a radiographic prognostication tool for BOS, which can used by pulmonologists at the bedside to provide timely counseling. 7 The group utilizes a simplified Brody II scoring system, which was originally conceived to objectify severity of pulmonary abnormalities on chest computed tomography (CT) for patients with cystic fibrosis. 8 The Brody II score aims to quantify aspects of lung airway pathology including severity and extent of (a) central and peripheral bronchiectasis; (b) central and peripheral mucus plugging; (c) central and peripheral peribronchial wall thickening; (d) parenchymal changes (such as ground glass opacification, consolidation, blebs/bullae); and (e) air-trapping on expiratory images.…”
mentioning
confidence: 99%